Diagnosis dan Tatalaksana Terkini Gagal Jantung Akut - Saroinsong, Lifi; Jim, Edmond L.; Rampengan, Starry H. (e-CliniC, 2021)
Abstract: Acute heart failure (AHF) is an emergency condition with rapid onset that requires immediate treatment. Many factors play a role in the incidence of AHF thus providing various of clinical manifestation. Prevalence and mortality of AHF is still a major health problem in Asia with the highest prevalence rate. This study intended to determine the tests needed to establish a diagnosis and recent treatment needed for AHF. This was a literature review study. The results showed the development of diagnosis and management of AHF based on the class of recommendation and levels of evidence updated by ESC 2016 and ACC/AHA/HFSA 2017. Furthermore, 4 journals discussed the development of troponin as biomarkers, multiple biomarkers, miRNA, and Lung Ultrasound (LUS). The development in AHF management was using tolvaptan, serelaxin, and neuromuscular electrical stimulation (NMES). In conclusion, diagnosis through anamnesis, physical examination, and supporting AHF can be done by understanding the causes of fluid retention and decreased cardiac output of the patient, therefore, it can provide pharmacological and non-pharmacological treatment appropriately.Keywords: diagnosis, treatment, acute heart failureÂ Abstrak: Gagal jantung akut (GJA) merupakan kondisi darurat dengan tipe serangan yang cepat sehingga membutuhkan penanganan segera. Banyak faktor yang berperan dalam kejadian GJA sehingga memberikan gambaran klinis yang beragam. Prevalensi dan mortalitas GJA di dunia terus mengalami peningkatan dan masih merupakan masalah kesehatan utama di Asia. Penelitian ini bertujuan untuk mengetahui pemeriksaan yang diperlukan untuk menegakkan diagnosis GJA dan perkembangan tatalaksana terkini GJA. Jenis penelitian ialah literature review. Hasil penelitian mendapatkan perkembangan diagnosis dan tatalaksana GJA berdasarkan kelas rekomendasi dan tingkatan bukti yang diperbaharui oleh ESC 2016 dan ACC/AHA/HFSA 2017. Selain itu, 4 jurnal membahas perkembangan penggunaan biomarker troponin, biomarker multipel, miRNA, serta USG Paru. Perkembangan tatalaksana GJA menggunakan tolvaptan, serelaksin, dan neuromuscular electrical stimulation (NMES). Simpulan penelitian ini ialah penegakan diagnosis lewat anamnesis, pemeriksaan fisik dan penunjang GJA dapat dilakukan dengan memahami penyebab retensi cairan dan penurunan curah jantung pasien sehingga dapat memberikan tatalaksana farmakologis dan non-farmakologis dengan tepat.Kata kunci: diagnosis, tatalaksana, gagal jantung akutÂ